The double call for joy, "Rejoice and be glad" (Matt. 5:12), as conclusion of the Matthean macarisms - F. P. Viljoen (Acta Theologica)
In contrast to Luke, for whom joy and rejoicing are major motifs, Matthew rarely writes about them. This may reflect the antagonistic environment in which the Matthean community functioned. However, a few texts refer to joy: Matthew 2:10, 13:44 and, in particular, 5:12. This article explores the call for joy in Matthew 5:12 which takes up and interprets makarioi of the above beatitudes. Matthew 5:12 begins with a double call for joy: “Rejoice and be glad”, eliciting a liturgical response, such as “Hallelujah” or similar exclamations, and a life of faith from the audience or readers. This double call raises some questions. What is the relation between these two imperatives — are they more than mere duplication? What is the relation between this double call and the beatitude (macarism) of v. 11 and other beatitudes? Should vv. 11 and 12 be read as two beatitudes? How did beatitudes in general function as literary genre? What is the Sitz im Leben of Matthew’s beatitudes and what kind of response is required from the audience or readers? Does the response in Matthew reflect actual liturgical practice or is it merely a literary device? How can this call be applied to our present situation?